2013
DOI: 10.4172/2329-6798.1000111
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Sensor for Determination of Mercury in Contaminated Water

Abstract: In this research, we constructed chemical sensor for determining mercury in contaminated water because we needed fast, simple, low-cost, and accurate determination of mercury in different environmental systems. The constructed membrane composed of (Poly Vinyl Chloride) PVC as a matrix material, 1,5-diphenylthiocarbazone (dithizone) as electro active compound, and di-n-butyl phthalate (DBPH) as a plasticizer. The optimum membrane composition 30% PVC, 65% DBPH, 5% dithizone exhibited the better Nernstian respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Optimal working conditions for the potentiometric response of the electrode in terms of its membrane composition and the pH of the aqueous solution were investigated together with the characteristics of this electrode regarding linear working range, detection limit, lifetime and interferences. The advantages of this new electrode relative to those based on ionophores (such as crown ethers derivatives, [21][22][23][24][25][26] calixarene derivatives, [27][28][29] cryptand 22, 30 tetra-aza macrocycles [31][32][33] as well as other compounds [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] ) are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal working conditions for the potentiometric response of the electrode in terms of its membrane composition and the pH of the aqueous solution were investigated together with the characteristics of this electrode regarding linear working range, detection limit, lifetime and interferences. The advantages of this new electrode relative to those based on ionophores (such as crown ethers derivatives, [21][22][23][24][25][26] calixarene derivatives, [27][28][29] cryptand 22, 30 tetra-aza macrocycles [31][32][33] as well as other compounds [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] ) are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Other metal-sensitive sensors based on different polymeric membrane ion-selective electrodes incorporating ionophores, sensitive to different cations, have been widely reported in the literature [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Most of these sensors exhibit a near-Nernstian or Nernstian response to the different cations studied.…”
Section: Resultsmentioning
confidence: 99%
“…It was also observed that probability value (′p′ value) was greater than alpha (> 0.05) which provided the evidence that the proposed electrode can be suitably used to check the presence of Hg 2+ in the real samples. Comparability of proposed electrode with reported sensors selective for mercury ions: The working of proposed electrode was compared with the reported sensors selective for mercury [40][41][42][43][44] and found that electrode based on chromium(III) boratotungstophosphate was superior with respect to its properties (Table-11).…”
Section: Analytical Applicationsmentioning
confidence: 97%